Produção de embriões humanos através da injeção intracitoplasmática de espermatozóides obtidos do ejaculado, epidídimo ou testículo - Pimentel, Anita Mylius (2006)
This retrospective study compared rates of fertilization, cleavage and quality of human embryos obtained by intracytoplasmic sperm injection (ICSI), with sperm from ejaculate, epididymis and testis. A total of 398 cycles of patients with some kind of male infertility were included and 3991 oocytes were inseminated. The spermatozoa from epididymis and testis were surgically obtained. Fertilization and cleavage rates with sperm from ejaculate (75% and 73%, respectively) were higher (P<0,0001) than those with sperm from the testis (59,7% e 56,8%, respectively) and from epididymis (61,9% e 59,3%). The production of viable embryos (grade I and II) was higher (P=0,0135) when the oocytes where inseminated with ejaculate sperm (89,4%) in relation to sperm from epididymis (82,9%) and testis (85,7%).The percentages of pregnancy were not different among groups (37,8% EJAC group, 27,6% EPID and 36,8% TEST group). In conclusion, sperm from ejaculate have a higher production of viable embryos. However, when sperm from the testis and epididymis are used for ICSI, the production of viable embryos is also considerable and can be seen as success in the assisted reproduction techniques.